From Lexical Tone to Lexical Stress: A Cross-Language Mediation Model for Cantonese Children Learning English as a Second Language - Choi, William; Tong, Xiuli; Singh, Leher (Frontiers in Psychology, 2017)
This study investigated how Cantonese lexical tone sensitivity contributed to English lexical stress sensitivity among Cantonese children who learned English as a second language (ESL). Five-hundred-and-sixteen second-to-third grade Cantonese ESL children were tested on their Cantonese lexical tone sensitivity, English lexical stress sensitivity, general auditory sensitivity, and working memory. Structural equation modeling revealed that Cantonese lexical tone sensitivity contributed to English lexical stress sensitivity both directly, and indirectly through the mediation of general auditory sensitivity, in which the direct pathway had a larger relative contribution to English lexical stress sensitivity than the indirect pathway. These results suggest that the tone-stress association might be accounted for by joint phonological and acoustic processes that underlie lexical tone and lexical stress perception.